A mixed-method study of feasibility and acceptability of the Dapivirine vaginal ring among adolescent girls and young women (AGYW) in selected Zimbabwean districts. - Noah Taruberekera; Malvern Munjoma; Owen Mugurungi; Getrude Ncube; Miriam Mutseta; Munyaradzi Dhodho; Hanul Choi; Jabulani Mavudze; Tafara Moga; Blessing Mutede (PLOS Global Public Health)
The Dapivirine vaginal ring (DPV-VR) is an intravaginal silicone ring that delivers an antiretroviral drug (Dapivirine) directly to vaginal tissues for 28 days. This ring protects women against HIV during the receptive vaginal sex at the site of potential infection. In 2021, the WHO recommended DPV as an additional prevention method for high-risk women for HIV with other approaches. With its discreet usage and disposal, DPV-VR has become a preferred HIV method among young women in Sub-Saharan Africa with a prevalent patriarchal social structure that prevents women from making decisions on their bodily autonomy. This study is aimed to assess the acceptability and feasibility of introducing DPV-VR as an HIV prevention method among young women in Zimbabwe and assess motivations and barriers of DPV-VR uptake among target population. We conducted an open-label prospective cohort study from 26 April 2022 to 23 January 2023 across 8 districts in Zimbabwe. Sexually active HIV-negative women aged between 18 and 25 years who were identified as high risk were offered a choice of oral PrEP or DPV-VR. Participants who chose DPV-VR were followed up for six months to receive monthly ring replacement and measure feasibility and acceptability. In-depth interviews were conducted with recipients of care who discontinued, continued for six months, or seroconverted while enrolled in the study to understand their experiences. A minimum of five clients who seroconverted were interviewed to identify potential timeline of seroconversions and risky behaviors. A total of 1,596 eligible participants were enrolled to study, and 1206 (76%) received DPV-VR and 390 AGYW opted for oral PrEP. Continuation rates were comparable among two groups at one month at 83% in the DPV ring arm and 84% in the oral PrEP arm. At 6 months, 64% of DPV users continued, compared to 16% in the oral PrEP arm. Participants who preferred to self-insert the ring increased from 50% at one-month follow up to 85.4% at 6 months. Seroconversion rates were comparable across two groups, as 9 out of 1095 (0.82%) DPV-VR users were seroconverted compared to 2 out of 390 (0.51%) oral PrEP users (p=0.608). Some DPV users mentioned pelvic pain and lower abdominal pain as common side effects. In in-depth interviews, participants mentioned motivators for DPV uptake such as its discreet use and not having to take medication daily. They also recommended to develop rings that last longer than current 28-day lifespan for women in rural areas or mobile who do not have continuous access to resources. This research provides evidence of DPV-VR as an acceptable and feasible HIV prevention in LMICs. Clients found it easy to insert the ring by themselves, and it provides a discreet way to protect themselves from HIV infection. Nevertheless, there are social barriers that hinder women's decision-making power in protecting their bodies. Therefore, it is recommended to conduct further studies to identify solutions for barriers and scale-up.